Pengaruh Efikasi Diri dan Literasi Digital terhadap Komitmen Profesi Guru (Studi Kasus di Sekolah Tarakanita Pluit Jakarta) - Cahyaningrum, Vincentia Dea; Tambunan, Witarsa; Tampubolon, Hotner (FONDATIA, 2023)
Self-efficacy or efficacy is a person's belief in their own motivation in carrying out certain tasks, including considerations of self-efficacy and confidence in information technology. The research aims to a) prove the effect of self-efficacy on the professional commitment of teachers at the Tarakanita Pluit School b) prove the influence of digital literacy on the professional commitment of teachers at the Tarakanita Pluit School c) prove the influence of self-efficacy and digital literacy on the professional commitment of teachers at the Tarakanita Pluit School . This research applies quantitative research methods with survey methods. This research is quantitative in nature and a survey uses questionnaires as a data collection tool. The research variables that will be studied are related variables, namely self-efficacy (X_1) and digital literacy (X_2) with a connecting variable, namely teacher professional commitment (Y). The results of this research are a) research states that the variables self-efficacy and digital competence are not the only variables that influence a teacher's professional commitment. b) The proportion of self-efficacy is moderate, namely only 31.6% of teachers' professional commitment, which can reduce teachers' professional commitment if educational institutions cannot foster the spirit of teachers' professional commitment, especially if the staff themselves do not have self-efficacy when working c) Low levels of digital literacy, accounting for only 16.4% of teachers' professional engagement, can hinder staff performance. The results of the study show that teacher professional involvement supported by digital literacy increases the growth of teacher professional involvement.